Comparative studies of the influence of particle size on various pretreatments of rice husk by assessment of chemical and structural components and wastewater characteristics of liquid fraction - Shahabazuddin, Mohmmad; Banuvalli, Bhavana Karibasappa; Mulik, Nagesh; Pande, Ashwini; Bokade, Vijay; Mudliar, Sandeep Narayan (Biomass Conversion and Biorefinery, 2023)
The dilute acid (DA), steam explosion (SE), and a 2-step: steam explosion followed by alkali (SEA) were evaluated for pretreatment of rice husk. The maximum hemicellulose and lignin removal via degradation and dissolution was observed for SEA pretreatment, enabling higher cellulose enrichment (up to 44% w/w) and recovery (up to 78%). The hemicellulose solubilization was >90% for all the pretreatments, while maximum lignin removal (up to 62%) was observed for SEA pretreatment. The particle size in the range of 0.3-0.6 mm enabled higher pretreatment efficiencies in terms of cellulose enrichment. The liquid fraction obtained after DA pretreatment indicated higher COD values (20800-24440 mg/L) as compared to SEA (7800-11400 mg/L) due to lower cellulose recoveries in DAP (54-68%). SEM analysis of the biomass indicated disrupted regions with multiple pores. FTIR analysis revealed cleavage of lignin side chains, and XRD analysis confirmed the increase in cellulose crystallinity post-pretreatment.
Keywords: Lignocellulosic crop residues; Liquid-waste characterization; Particle size; Rice husk biomass; Steam explosion pretreatment